The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1111/ppa.13823
|View full text |Cite
|
Sign up to set email alerts
|

Survey of viruses and vectors in tomato plants, alternative hosts and weeds in the state of Santa Catarina, Brazil

Eduardo Silva Gorayeb,
Samara Campos do Nascimento,
Alba Nise Mericia Rocha dos Santos
et al.

Abstract: Santa Catarina is an important tomato‐producing state in Brazil, but there is little data regarding the prevalence and characterization of viruses and insect vectors in tomato plants in this state. This study surveyed viruses and their vectors in commercial tomato‐producing areas, as well as alternative hosts and weeds in the surrounding areas. Sixty‐five samples of young leaves were collected between 2019 and 2023, and viruses were detected with generic or specific PCR primers targeting several virus genera. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…ToSRV was previously registered in Santa Catarina in the year 2006 [ 64 ] and also in Paraná in 2014 [ 65 ]. A recent survey in the state of Santa Catarina found that ToSRV is limited to the metropolitan region of Florianópolis [ 66 ]. We also provide the first confirmation of tomato plants infected by ToMoLCV across all states of the South regions (Paraná, Rio Grande do Sul, and Santa Catarina).…”
Section: Discussionmentioning
confidence: 99%
“…ToSRV was previously registered in Santa Catarina in the year 2006 [ 64 ] and also in Paraná in 2014 [ 65 ]. A recent survey in the state of Santa Catarina found that ToSRV is limited to the metropolitan region of Florianópolis [ 66 ]. We also provide the first confirmation of tomato plants infected by ToMoLCV across all states of the South regions (Paraná, Rio Grande do Sul, and Santa Catarina).…”
Section: Discussionmentioning
confidence: 99%